Autoimmune hepatitis. Clinical case - Usachova, Anna; Onyshchuk, Lyudmila (The Ukrainian Scientific Medical Youth Journal, 2025)
аutoimmune hepatitis is a rare disease of the liver that is charachterised by heteromorphism of a clinical picture, antinuclear antibody presence, hyperhammaglobulinemia, histological changes of liver. The etiology of autoimmune hepatitis is unknown, but the influence of genetic and environmental factors is assumed. The course of the disease varies from completely asymptomatic to the development of liver failure. This disease more often affects women and can debut at any age. There are two types of autoimmune hepatitis depending on the type of antibodies detected in the patient. First type is charachterised by presence of antinuclear antibodies, anti-smooth muscle antibodies, antibodies against soluble liver antigen/ liver pancreas antigen. In the second type, antibodies to liver cell microsomes, antibodies to liver cytosol-1 are observed. In both variants, either one type of antibody or all of them can be present. The aim of the study is to describe a clinical case of autoimmune hepatitis in the context of modern requirements for diagnosis and treatment. A patient born in 1960 who complained of yellow skin, weakness, sweating, increased body temperature was examined at the Medico Medical Center. During further laboratory and instrumental studies, the syndrome of cytolysis and changes in the organs of the abdominal cavity were revealed, which required the exclusion of cancer of the head of the pancreas, acute cholecystitis. During the surgeon's consultation, these pathologies were excluded. The viral, parasitic, toxic, medicinal nature of the disease was not confirmed, so there was a suspicion of the autoimmune genesis of the disease. Antinuclear antibodies were detected in the patient's blood serum, which is one of the criteria for establishing a diagnosis of autoimmune hepatitis, so the task was to confirm or refute this diagnosis. With the help of ultrasound elastography and liver biopsy, characteristic changes were revealed, such as foci of inflammation and necrosis, mainly plasmacytic inflammatory infiltration of liver tissue. A differential diagnosis was made with primary biliary cirrhosis, primary sclerosing cholangitis. A diagnosis of autoimmune hepatitis was established. Treatment with methylprednisolone was started, and the patient's condition and response to treatment are currently being monitored. Within a month of therapy, it was possible to achieve positive dynamics, which is manifested by the normalization of the level of alanine aminotransferase and aspartate aminotransferase. The further plan of treatment consists in gradually reducing the dose of methylprednisolone and achieving a stable remission of the patient. Autoimmune hepatitis should be included in the differential diagnosis if the patient has signs of liver pathology of unknown origin. A comprehensive approach to diagnosis, which includes laboratory tests and a liver biopsy, allows choosing a treatment that will improve the patient's quality of life and allow to enter a stable remission.